2018
DOI: 10.3390/md16120498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Marine Microalga Chlorella pyrenoidosa Ethanol Extract on Lipid Metabolism and Gut Microbiota Composition in High-Fat Diet-Fed Rats

Abstract: Effects of marine microalga Chlorella pyrenoidosa 55% ethanol extract (CPE55) on lipid metabolism, gut microbiota and regulation mechanism in high fat diet-fed induced hyperlipidaemia rats were investigated. Structure characterizations of major compounds in CPE55 were determined by ultra-performance liquid chromatography-quadrupole/time of flight mass spectrometry (UPLC-Q-TOF-MS/MS). The compositions of gut microbiota in rats were analyzed by high-throughput next-generation 16S rRNA gene sequencing. Oral admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…In contrast, the abundance of the Alistipes genus was significantly decreased in the HL group compared to HC. The abundance of Alistipes , which belongs to the Bacteroidetes phylum, was lower in rodent models with high fat diet-induced hyperlipidemia [ 28 , 29 ]. In addition, the levels of this genus were also significantly decreased in obese Mexican individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the abundance of the Alistipes genus was significantly decreased in the HL group compared to HC. The abundance of Alistipes , which belongs to the Bacteroidetes phylum, was lower in rodent models with high fat diet-induced hyperlipidemia [ 28 , 29 ]. In addition, the levels of this genus were also significantly decreased in obese Mexican individuals [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 The genus Romboutsia was isolated from the digestive samples of ileum for the first time in 2014. 52 For the past few years, studies have shown that Romboutsia is negatively correlated with fasting glucose, insulin, and HDL-C, and positively correlated with serum TC, TG, and LDL-C. [53][54][55][56] A recent study found Romboutsia increased in T2DM mice model. 57 Our experiment firstly illustrated a clear correlation between Romboutsia and T2DM in a diabetes rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Several microbes, including Turicibacter, Roseburia, Lachnospira and Romboutsia, showed positive relationships with abnormal serum triglyceride, total cholesterol and low‐density lipoprotein (LDL) levels, and a negatively correlated relationship with the serum high‐density lipoprotein (HDL) levels. By contrast, the abundance of Ruminococcus_1, Rikenella, Bacteroides, Butyrivibrio and Alistipes was negatively correlated with serum triglyceride, total cholesterol and LDL levels but were positively correlated with HDL levels (Wan, et al , ). Gut colonization with bacteria of the phylum Bacteroidetes altered bile salt hydrolase features, leading to changes in the gut bile acid composition that affected host metabolism and gene expression (Yao, et al , ) (Fig.…”
Section: The Link Between the Gut Microbiota And Cvd‐related Risk Facmentioning
confidence: 99%